Polymerization modified organic lithium ion battery diaphragm as well as preparation method and application thereof
Through the use of modified organic adhesives, the problem of limited heat resistance of existing ceramic coated separators under high temperature conditions has been solved, and the high heat resistance and excellent adhesive properties of lithium-ion battery separators are achieved, ensuring the stability of the separators under extreme high temperature conditions.
Patent Information
- Application Number
- CN202411853137.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-16
AI Technical Summary
The existing ceramic coated diaphragms have limited heat resistance under high temperature conditions and cannot take into account both high temperature resistance and adhesive properties.
Using a modified organic adhesive, a slurry with excellent heat resistance and adhesive properties was prepared by copolymerization of polyhydroxyimide and vinylidene fluoride copolymer, and it was coated on the base film by point coating or roll coating technology.
The stable performance of lithium-ion battery separators under extremely high temperature conditions is achieved, the heat resistance and adhesive strength of the separators are enhanced, and the decomposition or failure of the separators at high temperatures is avoided.
Smart Images

Figure CN119812671A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery separators, and in particular relates to a polymer-modified organic lithium-ion battery separator and a preparation method and application thereof. Background Art
[0002] Lithium-ion battery separator is one of the core components of lithium-ion batteries. Its performance has a crucial impact on the overall performance of lithium-ion batteries, and it is also one of the important factors restricting the development of high-performance lithium-ion battery technology. At present, the battery technology of new energy vehicles has made rapid progress, and higher requirements have been put forward for the heat resistance and adhesion performance of ultra-thin separators. At present, the water-based ceramic coating is a mixture of polymer adhesives and ceramic particles in the slurry, which is coated on at least one side of the polyethylene base film. After drying, a rigid inorganic coating layer is formed on the surface of the base film, which can play a certain role in inhibiting the shrinkage of the separator. However, the high temperature resistance of the existing ceramic coated separator is limited, and it is impossible to achieve both high temperature resistance and adhesion performance. Even if the ratio of polymer adhesives and ceramic particles in the slurry is increased, it is difficult to further improve the high temperature resistance, and the ceramic separator and the pole piece do not have sufficient adhesion. At present, the heat resistance of the water-based ceramic coating is limited, and it is urgent to develop a separator with excellent heat resistance and adhesion performance. Summary of the invention
[0003] In view of the deficiencies in the prior art, an object of the present invention is to provide a lithium ion battery separator.
[0004] Another object of the present invention is to provide a method for preparing a modified organic adhesive.
[0005] Another object of the present invention is to provide a slurry.
[0006] The purpose of the present invention is achieved through the following technical solutions.
[0007] A lithium ion battery separator comprises: a base film and a coating on the base film, wherein the coating comprises: a modified organic binder, a first auxiliary agent and a second auxiliary agent, wherein the first auxiliary agent is polymethylsiloxane, and the second auxiliary agent is sodium carboxymethyl cellulose, and the ratio of the modified organic binder, the first auxiliary agent and the second auxiliary agent is 1:(0.01-0.05):(1-2) by mass, and the structural formula of the modified organic binder is:
[0008]
[0009] , the degree of polymerization n3 is 1430~1455.
[0010] In the above technical solution, the number average molecular weight of the modified organic binder is 1.18 to 1.2 million.
[0011] The method for preparing the lithium ion battery separator comprises: coating the slurry on the base film, drying, obtaining a coating on the base film, and obtaining the lithium ion battery separator.
[0012] In the above technical solution, the coating method is one of spot coating and roller coating.
[0013] In the above technical solution, the thickness of the coating is 1 to 10 μm.
[0014] A method for preparing a modified organic adhesive comprises: mixing polyhydroxyimide, a vinylidene fluoride copolymer and a chain extender, and polymerizing them at -5 to 0°C for 2 to 10 hours under stirring conditions to obtain a modified organic adhesive, wherein the ratio of the polyhydroxyimide, the vinylidene fluoride copolymer and the chain extender is (0.1 to 0.2):1:0.05 in terms of the amount of the substances.
[0015] In the above technical solution, the chain extender is a mixture of one or more of dicyclohexylcarbodiimide (DCC), N,N-diisopropylcarbodiimide (DIC), carbodiimide hydrochloride (EDC) and 4-dimethylaminopyridine (DMAP).
[0016] In the above technical solution, the number average molecular weight of the polyhydroxyimide is 29670-32260, and the degree of polymerization (n1) is 56-62.
[0017] In the above technical solution, the number average molecular weight of the vinylidene fluoride copolymer is 985,000 to 996,000, the degree of polymerization (n2) is 2943 to 2977, and the vinylidene fluoride copolymer is copolymerized by vinylidene fluoride, hexafluoropropylene and acrylic acid.
[0018] In the above technical solution, the polymerization reaction is carried out at -5 to 0° C. for 2 to 10 hours under stirring conditions with a rotation speed of 40 to 45 r / min to obtain a modified organic adhesive.
[0019] In the above technical scheme, the method for preparing polyhydroxyimide is: 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (6FAP), terephthaloyl chloride (TPC) and a first solvent are mixed, and reacted at -5 to 0°C for 3 to 6 hours under stirring conditions to obtain polyhydroxyimide, wherein the ratio of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (6FAP) to terephthaloyl chloride (TPC) is 1: (1 to 1.05) in terms of the amount of the substance.
[0020] In the method for preparing polyhydroxyimide, the reaction is carried out at -5 to 0° C. for 3 to 6 hours under stirring conditions with a rotation speed of 40 to 45 r / min.
[0021] In the method for preparing polyhydroxyimide, the ratio of the amount of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (6FAP) to the volume of the first solvent is (0.1-0.12):120, the unit of the amount of the substance is mol, and the unit of the volume is mL.
[0022] In the method for preparing polyhydroxyimide, the first solvent is at least one of N,N-dimethylacetamide (DMAC) (water content ≤2000ppm), N-methylpyrrolidone (NMP) (water content ≤2000ppm), hexamethylphosphoramide (HMPA) (water content ≤2000ppm), 1,4-dioxane (DOX) (water content ≤2000ppm), diethylene glycol dimethyl ether (DGDE) (water content ≤2000ppm) and N,N-dimethylformamide (DMF) (water content ≤2000ppm).
[0023] In the above technical scheme, the method for preparing a vinylidene fluoride copolymer is: vinylidene fluoride, hexafluoropropylene, acrylic acid, an initiator and a second solvent are mixed, reacted at 120-130°C for 10-12 hours under stirring conditions, cooled to -5-0°C, an acyl chloride reagent is added, heated to 50-55°C and refluxed at 50-55°C for 6-8 hours to obtain a vinylidene fluoride copolymer. In terms of the amount of the substance, the ratio of vinylidene fluoride, hexafluoropropylene, acrylic acid, initiator and acyl chloride reagent is 1:0.3:(0.1-0.2):0.001:10.
[0024] In the method for preparing vinylidene fluoride copolymer, the acyl chloride reagent is thionyl chloride.
[0025] In the method for preparing a vinylidene fluoride copolymer, the initiator is tert-butyl peroxypentanoate, and the second solvent is acetonitrile (water content ≤ 2000 ppm).
[0026] In the method for preparing a vinylidene fluoride copolymer, the ratio of the molar fraction of vinylidene fluoride to the volume fraction of the second solvent is 1:(500-510), the unit of the molar fraction is mol, and the unit of the volume fraction is mL.
[0027] In the method for preparing vinylidene fluoride copolymer, the reaction is carried out at 120-130° C. for 10-12 hours under stirring conditions with a rotation speed of 40-45 r / min.
[0028] A slurry comprises: a modified organic binder, a first auxiliary agent and a second auxiliary agent, wherein the ratio of the modified organic binder, the first auxiliary agent and the second auxiliary agent is 1: (0.01-0.05): (1-2) by weight.
[0029] The method for preparing the slurry comprises: mixing the modified organic binder, the first auxiliary agent and the second auxiliary agent until they are uniform to obtain the slurry.
[0030] In the above technical solution, the modified organic binder, the first auxiliary agent and the second auxiliary agent are mixed, and mixed at a dispersion speed of 1200-2000 r / min and a stirring speed of 20-40 r / min for 1-2 hours until uniform to obtain a slurry.
[0031] The application of modified organic binder in improving the heat resistance of diaphragm, the structural formula of modified organic binder is:
[0032] , the degree of polymerization n3 is 1430~1455.
[0033] The application of modified organic binder in improving the adhesion of diaphragm, the structural formula of modified organic binder is:
[0034] , the degree of polymerization n3 is 1430~1455.
[0035] The main chain of the modified organic adhesive of the present invention includes a vinylidene fluoride segment, a hexafluoropropylene segment and an acrylic acid segment, and the side chain includes an imide segment. In terms of structural design, not only the selection and ratio of monomers are emphasized, but also the synergistic effect between the main chain and the side chain is emphasized; the lithium-ion battery separator has both high heat resistance and excellent bonding performance. The high heat resistance is due to the presence of fluorinated components in the main chain and the addition of side chains, and the excellent bonding strength: the acrylic acid segment, as part of the main chain, gives the lithium-ion battery separator good bonding strength. The lithium-ion battery separator of the present invention maintains stable physical and chemical properties under extremely high temperature conditions and is not easy to decompose or fail.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] The present invention prepares a modified organic adhesive by polymerizing a vinylidene fluoride copolymer and a polyhydroxyimide by polymerization to obtain a modified organic adhesive, wherein the polyhydroxyimide contains an aromatic ring rigid skeleton, and the introduction of the aromatic ring rigid skeleton enhances the heat resistance of the lithium ion battery separator, and the trifluoromethyl group reduces the molar polarization α of the lithium ion battery separator, thereby reducing the dielectric constant and dielectric loss of the lithium ion battery separator, thereby increasing the breakdown voltage of the separator, and the main chain of the modified organic adhesive provides excellent bonding performance, and the hydroxyl group in the side chain can form an intermolecular hydrogen bond to enhance the bonding performance of the lithium ion battery separator, and further enhance the bonding force of the separator. The slurry of the present invention does not need to be added with water. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1is the reaction formula for synthesizing polyhydroxyimide;
[0039] Figure 2 is the reaction formula for synthesizing vinylidene fluoride copolymer;
[0040] Figure 3 is the reaction formula for synthesizing modified organic adhesive;
[0041] Figure 4 is the ATR spectrum of the modified organic adhesive;
[0042] Figure 5 This is the SEM image of the separator prepared in Example 5. DETAILED DESCRIPTION
[0043] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0044] The shrinkage rate is tested according to GB / T 36363-2018.
[0045] The breakdown voltage is tested according to GB-T 13542.2-2009.
[0046] Hot-pressed positive electrode sheet bonding strength: the size of the cut diaphragm is 25*150mm, and the size of the positive electrode sheet is 25*150mm; the temperature of the hot press is adjusted to 80℃ and the pressure is 1000KG, and the diaphragm and the positive electrode sheet are preheated for 1s and hot pressed for 1s using the hot press; the hot-pressed positive electrode sheet bonding strength is tested using an electronic tensile testing machine, and the diaphragm and the positive electrode sheet are peeled off until the stretching distance of the electronic tensile testing machine is 50mm, the speed of the electronic tensile testing machine is 300mm / min, the peeling degree is 180°, the hot-pressed positive electrode sheet bonding strength = peeling force divided by the stretching distance of the electronic tensile testing machine, peeling force: the average value of the force collected by the electronic tensile testing machine during the peeling process of the diaphragm and the positive electrode sheet, the hot-pressed positive electrode sheet bonding strength test is calculated based on the data with a stretching distance between 10 and 40mm, that is, the hot-pressed positive electrode sheet bonding strength = peeling force with a stretching distance between 10 and 40mm divided by 30mm. The positive electrode is ternary lithium nickel cobalt aluminum oxide (LiNi 0.8 Co 0.15 Al 0.05 O2) pole piece.
[0047] Hot-pressed negative electrode bonding strength: The test method is basically the same as the "hot-pressed positive electrode bonding strength", the difference is that the "positive electrode" is replaced by the "negative electrode", and the negative electrode is a carbon-based graphite electrode (carbon content 91%).
[0048] In the following embodiments, the base film is a wet-process polyethylene film, the thickness of the base film is 7.1 μm (it should be noted that other thicknesses may also be used), the air permeability is 71 Sec / 100 ml, and the thickness in this patent is tested in accordance with GBT 36363-2018.
[0049] The raw material information involved in the following examples is as follows:
[0050] Polymethylsiloxane: colorless transparent liquid, number average molecular weight is 19823, density is 0.965g / cm 3 , Fuchen Chemical Reagent Co., Ltd.
[0051] Sodium carboxymethyl cellulose: light yellow powder, viscosity 400-800 cP (2% soluble in water test at 25°C), produced by Bid Pharmaceutical Co., Ltd., Pudong New Area, Shanghai.
[0052] 4-Dimethylaminopyridine (DMAP): C7H 10 N2, molecular weight 122.17 g / mol, white powder, melting point 109 ° C, boiling point 211 ° C, density 1.0 g / cm 3 (25℃), flash point is 110℃, Bid Pharmaceutical Industry, Pudong New District, Shanghai.
[0053] 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (6FAP): white powder, molecular formula C 15 H 12 F6N2O2, molecular weight is 366.26. Melting point is 245℃, boiling point is about 411.3℃. Flash point is 202.6℃, density is 1.545g / cm 3 (25℃), purity 98%, Bailingwei Technology Co., Ltd.
[0054] Terephthaloyl chloride (TPC): molecular formula is C8H4Cl2O2, molecular weight is 203.0g / mol, colorless transparent crystalline powder, melting point is 79℃. Boiling point is 266℃. Density is 1.34g / cm 3 (25℃), purity 96%, Tianjin Guangfu Fine Chemical Research Institute.
[0055] Vinylidene fluoride: The molecular weight of vinylidene fluoride is 64.0341g / mol. The molecular formula is C2H2F2, the melting point is -144℃, the boiling point is -83℃. The flash point of vinylidene fluoride is lower than -60℃. Tianjin Jiangtian Chemical Co., Ltd.
[0056] Hexafluoropropylene: Chemical formula: C3F6. Molecular weight: 150.023. Density: 1.583g / cm 3 (Liquid). Melting point: -153°C. Boiling point: -28°C. Tianjin Jiangtian Chemical Co., Ltd.
[0057] Acrylic acid: Shanghai Aladdin Reagent. Molecular weight: 72.06. Colorless liquid with pungent odor. Melting point: 13°C. Boiling point: 140.9°C. Relative density: 1.051 g / cm 3 (Water = 1). Flash point: 54°C.
[0058] Tert-butyl peroxypentanoate: Ron's reagent, chemical formula: C9H 18 O3. Molecular weight is 174.237. Tert-butyl peroxyvalerate is a colorless liquid at room temperature. Density is 0.854 g / cm 3 (25℃). The melting point of tert-butyl peroxypentyvalerate is -17℃. The boiling point of tert-butyl peroxypentyvalerate is 182.5℃. The flash point is 68℃.
[0059] Sulfonyl chloride: Fuchen Chemical Reagent Co., Ltd. The molecular formula of thionyl chloride is SOCl2, and its relative molecular mass is 118.97. Sulfonyl chloride is a light yellow liquid. The melting point of thionyl chloride is -105℃, the boiling point is 78.8℃, and the density is 1.638g / cm 3 (25℃).
[0060] Example 1
[0061] A method for preparing slurry comprises: mixing a modified organic binder, a first auxiliary agent and a second auxiliary agent, stirring for 2 hours at a dispersion speed (rotation) of 2000 r / min and a stirring speed (revolution) of 40 r / min until uniform, to obtain slurry, wherein the first auxiliary agent is polymethylsiloxane, and the second auxiliary agent is sodium carboxymethyl cellulose, and the ratio of the modified organic binder, the first auxiliary agent and the second auxiliary agent is 1:0.05:2 in terms of mass fractions.
[0062] The preparation method of a modified organic adhesive comprises: pumping a polyhydroxyimide (with a number average molecular weight of 32,260) obtained in the second polymerization reactor and a vinylidene fluoride copolymer (with a number average molecular weight of 996,000) obtained in the first polymerization reactor into a third polymerization reactor through a bottom diaphragm pump, adding a chain extender, and reacting at -5°C for 10 hours under a stirring condition of a rotation speed of 40 r / min to obtain a modified organic adhesive, wherein the ratio of the polyhydroxyimide, the vinylidene fluoride copolymer and the chain extender is 0.1:1:0.05 in terms of the amount of the substance, and the chain extender is 4-dimethylaminopyridine (DMAP).
[0063] The method for preparing polyhydroxyimide is as follows: 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (6FAP), terephthaloyl chloride (TPC) and a first solvent are added into a second polymerization reactor, and reacted at -5°C for 6 hours under a stirring condition with a rotation speed of 45 r / min to obtain polyhydroxyimide, wherein the ratio of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (6FAP) to terephthaloyl chloride (TPC) is 1:1.05, the ratio of the amount of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (6FAP) to the volume of the first solvent is 0.12:120, the unit of the amount of the substance is mol, the unit of the volume is ml, and the first solvent is NMP (water content 1800 ppm).
[0064] The method for preparing a vinylidene fluoride copolymer is as follows: vinylidene fluoride, hexafluoropropylene, acrylic acid, an initiator and a second solvent are added to a first polymerization reactor for copolymerization, reacted at 130°C for 12 hours under a stirring condition of a rotation speed of 45 r / min, cooled the first polymerization reactor to -5°C after 12 hours, added an acyl chloride reagent, heated to 50°C and refluxed at 50°C for 6 hours to obtain a vinylidene fluoride copolymer, wherein the ratio of vinylidene fluoride, hexafluoropropylene, acrylic acid, initiator and acyl chloride reagent is 1:0.3:0.2:0.001:10 in terms of molar fraction, the acyl chloride reagent is thionyl chloride (molecular weight of 118.97), the initiator is tert-butyl peroxypentytivalate, the second solvent is acetonitrile (water content of 1800 ppm), the ratio of the molar fraction of vinylidene fluoride to the volume fraction of the second solvent is 1:500, the unit of the molar fraction is mol, and the unit of the volume fraction is ml.
[0065] The number average molecular weight of the modified organic adhesive prepared in Example 1 is 1.2 million.
[0066] Example 2
[0067] A method for preparing a slurry is basically the same as Example 1, except that: "by mass, the ratio of the modified organic binder, the first auxiliary agent and the second auxiliary agent is 1:0.05:2" is replaced by "by mass, the ratio of the modified organic binder, the first auxiliary agent and the second auxiliary agent is 1:0.01:1".
[0068] Example 3
[0069] A method for preparing slurry is basically the same as that of Example 1, except that the polyhydroxyimide is different. Example 3 The method for preparing polyhydroxyimide is as follows: 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (6FAP), terephthaloyl chloride (TPC) and a first solvent are added into a second polymerization reactor, and reacted at -5°C for 3 hours under a stirring condition of a rotation speed of 40 r / min to obtain polyhydroxyimide (number average molecular weight of 30561). In terms of the amount of substance, the ratio of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (6FAP) to terephthaloyl chloride (TPC) is 1:1, the ratio of the amount of substance of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (6FAP) to the volume of the first solvent is 0.10:120, the unit of the amount of substance is mol, the unit of the volume is ml, and the first solvent is DMF (water content: 1800 ppm).
[0070] The number average molecular weight of the modified organic adhesive prepared in Example 3 is 1.18 million.
[0071] Example 4
[0072] A method for preparing slurry is basically the same as that of Example 1, except that the vinylidene fluoride copolymer is different. Example 4 The method for preparing a vinylidene fluoride copolymer is as follows: vinylidene fluoride, hexafluoropropylene, acrylic acid, an initiator and a second solvent are added to a first polymerization reactor for copolymerization, reacted at 120°C for 10 hours under a stirring condition of a rotation speed of 40 r / min, and after 10 hours, the first polymerization reactor is cooled to 0°C, an acyl chloride reagent is added, heated to 50°C and refluxed at 50°C for 6 hours to obtain a vinylidene fluoride copolymer (number average molecular weight of 990,000). In terms of the amount of substance, the ratio of vinylidene fluoride, hexafluoropropylene, acrylic acid, initiator and acyl chloride reagent is 1:0.3:0.1:0.001:10, the acyl chloride reagent is thionyl chloride (molecular weight of 118.97), the initiator is tert-butyl peroxypentylaric acid, the second solvent is acetonitrile (water content of 1800ppm), the ratio of the amount of vinylidene fluoride to the volume of the second solvent is 1:500, the unit of the amount of substance is mol, and the unit of the volume is ml.
[0073] The number average molecular weight of the modified organic adhesive prepared in Example 4 is 1.19 million.
[0074] Example 5
[0075] A method for preparing a lithium-ion battery separator comprises: pumping the slurry prepared in Example 1 into a dot coating structure through a slurry pump, coating on both sides of a base film, drying at 80° C. for 10 minutes, obtaining a coating on the base film, and obtaining a lithium-ion battery separator. The coating dots are circular, the diameter of the coating dots is 400 μm, the coating dots are arranged in a square, and the side length of the square is 500 μm.
[0076] Example 6
[0077] A method for preparing a lithium-ion battery separator comprises: pumping the slurry prepared in Example 1 into a gravure roller coating structure (the depth of the gravure roller is 5 μm) through a slurry pump, coating it on both sides on a base film, drying it at 80° C. for 10 minutes, obtaining a coating on the base film, and obtaining a lithium-ion battery separator.
[0078] Example 7
[0079] A method for preparing a lithium-ion battery separator is basically the same as that of Example 5, except that "the slurry prepared in Example 1" is replaced by "the slurry prepared in Example 2".
[0080] Example 8
[0081] A method for preparing a lithium-ion battery separator is basically the same as that of Example 5, except that "the slurry prepared in Example 1" is replaced by "the slurry prepared in Example 3".
[0082] Example 9
[0083] A method for preparing a lithium-ion battery separator is basically the same as that of Example 5, except that "the slurry prepared in Example 1" is replaced by "the slurry prepared in Example 4".
[0084] Comparative Example 1
[0085] A method for preparing a lithium-ion battery separator is basically the same as that of Example 5, except that a different slurry is used.
[0086] The method for preparing the slurry in Comparative Example 1 comprises: mixing water, PVDF powder (purchased from Sinochem Blue Sky Fluorine Materials Co., Ltd., PVDF powder is a copolymer of vinylidene fluoride and hexafluoropropylene, melting point 1151°C, particle size D50=6 μm), a first auxiliary agent and a second auxiliary agent, stirring at a dispersion speed of 2000 r / min and a stirring speed of 40 r / min for 2 hours until uniform, to obtain a slurry, wherein the first auxiliary agent is polymethylsiloxane, and the second auxiliary agent is sodium carboxymethyl cellulose, and the ratio of water, PVDF powder, the first auxiliary agent and the second auxiliary agent is 10:1:0.05:2 in parts by mass.
[0087] Comparative Example 2
[0088] A method for preparing a lithium-ion battery separator is basically the same as that of Example 6, except that "the slurry prepared in Example 1" is replaced by "the slurry prepared in Comparative Example 1".
[0089] Comparative Example 3
[0090] A method for preparing a lithium-ion battery separator is basically the same as Example 5, the only difference being that the modified organic binder in the slurry used is different, and the number average molecular weight of the modified organic binder in Comparative Example 3 is 830,000.
[0091] The method for preparing the modified organic adhesive in Comparative Example 3 comprises: mixing polyhydroxyimide, vinylidene fluoride copolymer (the same as the vinylidene fluoride copolymer in Example 1) and 4-dimethylaminopyridine (DMAP), reacting at 0° C. for 10 hours under stirring conditions at a speed of 40 r / min, to obtain the modified organic adhesive of Comparative Example 3, wherein the ratio of polyhydroxyimide, vinylidene fluoride copolymer and 4-dimethylaminopyridine (DMAP) is 0.1:1:0.05 in terms of the amount of the substance, wherein the method for preparing the polyhydroxyimide is: mixing 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (6FAP), terephthaloyl chloride (TPC) and The first solvent was added into a polymerization reaction kettle, and the reaction was carried out at 25° C. for 1 h under a stirring condition with a rotation speed of 20 r / min to obtain polyhydroxyimide (number average molecular weight of 19149). In terms of the amount of substance, the ratio of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (6FAP) to terephthaloyl chloride (TPC) was 1:0.9, the ratio of the amount of substance of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (6FAP) to the volume of the first solvent was 0.12:120, the unit of the amount of substance was mol, the unit of the volume was ml, and the first solvent was NMP (water content: 1800 ppm).
[0092] The single-side coating amount of the lithium-ion battery separators prepared in Examples 5-9 and Comparative Examples 1-3 was 0.9 g / ㎡.
[0093] Table 1
[0094]
[0095]
[0096] Figure 1 is the reaction formula for synthesizing polyhydroxyimide; Figure 2 is the reaction formula for synthesizing vinylidene fluoride copolymer; Figure 3 is the reaction formula for synthesizing modified organic adhesive; Figure 4 is the ATR spectrum of the modified organic binder. Figure 4Medium 3093-2850cm -1 There is an OH stretching vibration absorption peak at 1747 cm -1 and 1598cm -1 There are amide bond C=O stretching vibration absorption peak and NH bending vibration absorption peak at 3425cm -1 There is an NH stretching vibration absorption peak at 1396cm -1 With CN stretching vibration, 1178cm -1 The presence of CF stretching vibration peaks indicates that the target modified organic binder was successfully synthesized.
[0097] Figure 5 This is the SEM image of the separator prepared in Example 5.
[0098] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A modified organic adhesive, characterized in that: The structural formula of the modified organic binder is: , The degree of polymerization n3 is 1430-1455.
2. A method for preparing a modified organic adhesive, characterized in that: include: The polyhydroxyimide, the vinylidene fluoride copolymer and the chain extender are mixed, and a polymerization reaction is carried out at -5 to 0°C for 2 to 10 hours under stirring conditions to obtain a modified organic adhesive, wherein the ratio of the polyhydroxyimide, the vinylidene fluoride copolymer and the chain extender is (0.1 to 0.2): 1: 0.05 in terms of the amount of the substance.
3. The preparation method according to claim 2, characterized in that: The structural formula of polyhydroxyimide is: The degree of polymerization n1 is 56-62.
4. The preparation method according to claim 2, characterized in that: The structural formula of vinylidene fluoride copolymer is: The degree of polymerization n2 is 2943~2977.
5. A lithium ion battery separator, characterized in that: include: A base film and a coating on the base film, wherein the coating comprises: a modified organic adhesive, a first auxiliary agent and a second auxiliary agent, wherein the first auxiliary agent is polymethylsiloxane, and the second auxiliary agent is sodium carboxymethyl cellulose. The ratio of the modified organic adhesive, the first auxiliary agent and the second auxiliary agent is 1:(0.01-0.05):(1-2) by weight, and the modified organic adhesive is one of the modified organic adhesives obtained by the preparation method described in claim 1 and claims 2-4.
6. The lithium ion battery separator according to claim 5, characterized in that: The coating has a thickness of 1 to 10 μm.
7. A method for preparing a lithium ion battery separator according to any one of claims 5 to 6, characterized in that: include: The slurry is coated on a base film and dried to obtain a coating on the base film to obtain a lithium-ion battery separator.
8. A slurry, characterized in that: include: The modified organic binder, the first auxiliary agent and the second auxiliary agent are in a ratio of 1:(0.01-0.05):(1-2) by mass. The modified organic binder is one of the modified organic binders obtained by the preparation method described in claim 1 and claims 2-4.
9. The method for preparing the slurry according to claim 8, characterized in that: include: The modified organic binder, the first auxiliary agent and the second auxiliary agent are mixed until uniform to obtain slurry.
10. Use of a modified organic adhesive in improving the heat resistance and / or adhesion of a separator, characterized in that: The modified organic adhesive is one of the modified organic adhesives obtained by the preparation methods described in claim 1 and claims 2 to 4.
Citation Information
Patent Citations
Lithium ion battery diaphragm, preparation method thereof and lithium ion battery
CN114784363A
High-cohesiveness diaphragm and preparation method thereof
CN116613464A
Lithium battery diaphragm based on reaction control agent and preparation method thereof
CN117004017A
Fluororesin-containing adhesive for rebase material
JP2004203830A